The causal effect of paternal unemployment on children's personality - Viola Angelini; Marco Bertoni; Luca Corazzini (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Using longitudinal data from the German Socio-Economic Panel (SOEP), we show that paternal unemployment has a surprisingly positive causal effect on the "Big 5" personality traits of children aged 17 to 25. In particular, our results from longitudinal value-added models for personality suggest that paternal unemployment makes children significantly more conscientious and less neurotic. Our results are robust to different estimation methods and to selection on unobservables. Furthermore, these effects are stronger for girls and for children whose mothers are employed.
Keywords: J24; J13; J64; C33; 330; personality traits; unemployment; household behavior; SOEP